The effect of substrate composition on the activity of amylase and cellulase by Trichoderma harzianum strains under solid state fermentation - Toga Pangihotan Napitupulu; Nathaniel Reinhart Silaban; Atit Kanti; I Made Sudiana (Microbiology Division, Research Center for Biology, Indonesian Institute of Sciences, 2019)
Trichoderma harzianum is a filamentous fungus that has been known to have biocontrol and plant growth-promoting ability. However, the propagation of this fungus particularly through solid state fermentation (SSF) and characterization of its enzyme activity as one the indicator of quality of fermentation process are still needed to be explored further. Rice grain and its derivative products have economically as well as nutrient composition features beneficial as substrates of fungal propagation through SSF. Therefore, the aim of this study was to investigate the effect of white rice, rice bran, and combination of white rice and rice bran on the activity of amylase and cellulase by Trichoderma harzianum strains under SSF. Two strains of the fungus, InaCC F116 and InaCC F89, as well as their consortium were employed as fungal inoculants. After closed fermentation in dark chamber at 30 ± 1°C for 7 days, the activity of amylolytic as well as cellulolytic enzyme was assayed. The result showed that the presence of rice bran as a substrate increased the activity of crude amylase and crude cellulase. In all substrates, the strain F116 has low activity of both enzymes. The fungal consortium improves the activity of crude enzymes in all substrates. Therefore, the amylase and cellulase activity by T. harzianum in SSF condition were strain- as well as substrate-dependent.